2013
DOI: 10.1038/ni.2757
|View full text |Cite
|
Sign up to set email alerts
|

Paired immunoglobulin-like receptor A is an intrinsic, self-limiting suppressor of IL-5–induced eosinophil development

Abstract: Summary Eosinophilia is a hallmark characteristic of TH2-associated diseases and is critically regulated by the central eosinophil growth factor interleukin 5 (IL-5). Here we demonstrate that IL-5 activity in eosinophils was regulated by paired immunoglobulin-like receptor (PIR)-A and PIR-B. Upon self-recognition of β2M molecules, PIR-B served as a permissive checkpoint for IL-5-induced eosinophil development by suppressing the pro-apoptotic activities of PIR-A, which were mediated by the Grb2-Erk-Bim pathway.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 51 publications
(84 reference statements)
0
47
0
Order By: Relevance
“…Thus, Clm1 À/À eosinophils are hypersensitive to eotaxin stimulation and even low amounts of eotaxins could induce a strong chemotactic response. Taken together, our data suggest that similar to other ITIMbearing receptors such as PIR-B, which can regulate multiple cellular responses (e.g., chemotaxis, differentiation, innate immune responses, and adhesion) (45)(46)(47)(48)(49), CLM-1 may regulate a broader range of eosinophil responses and effector functions.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, Clm1 À/À eosinophils are hypersensitive to eotaxin stimulation and even low amounts of eotaxins could induce a strong chemotactic response. Taken together, our data suggest that similar to other ITIMbearing receptors such as PIR-B, which can regulate multiple cellular responses (e.g., chemotaxis, differentiation, innate immune responses, and adhesion) (45)(46)(47)(48)(49), CLM-1 may regulate a broader range of eosinophil responses and effector functions.…”
Section: Discussionmentioning
confidence: 82%
“…The ability to impede necrosis or redirect cell death from necrosis to apoptosis may lead to improved therapies in patients with eosinophilic conditions [137]. Ben Baruch-Morgenstern et al recently demonstrated that IL-5 activity in eosinophils was regulated by paired immunoglobulinlike receptors A and B, which may offer a way of regulating IL-5-induced expansion of the eosinophil [138]. CCchemokine receptor 3 (CCR3) is an eotaxin receptor known to be involved in eosinophil chemotaxis.…”
Section: Potential Future Treatment Targetsmentioning
confidence: 98%
“…Furthermore, PIRA also binds to Nogo, although the binding strength is 10-fold less and only detected for the third to sixth domains. The functional importance of the interaction with PIRA with Nogo has not been determined, but some functions of PIRA are known, such as regulating cytokine-driven maturation of eosinophils (66), providing some idea of the possibilities. The measured interaction with PIRA also begs the question of which other LILRs might interact with the NogoR ligands as well.…”
Section: Cns-derived Ligandsmentioning
confidence: 99%